Una nueva especie de Hyphessobrycon (Characiformes: Characidae) de la cuenca del río Telembí, vertiente sur del Pacífico, Colombia - García Alzate, Carlos A. (2013)
The genus Hyphessobrycon is included within the subfamily Tetragonopterinae. The species are generally small, do not exceed 70mm of standard length, are economically important as ornamental fish, with 128 valid species distributed from Southern Mexico to Rio La Plata in Argentina. The collections of fish were made with seines, in a single biotope, along shore in backwaters and working downstream. Measurements of the specimens were taken point to point with digital calipers. Observations of bone and cartilage structures were made on cleared and stained (C&S) specimens. The morphometric relationships between species were explored using a principal component analysis (PCA)using 21 variables. We described a new species, Hyphessobrycon chocoensis, from the Telembí River drainage of the Pacific versant of Colombia. The new species, Hyphessobrycon chocoensis, is distinguished from congeners not of the “flammeus” species group by: having a diffuse humeral spot, in lacking a dark spot on the dorsal fin and caudal peduncle. It is distinguished from members its species group by the number of rays in the dorsal fin (ii, 8, i), by the number of branched anal-fin rays (25-26) and by having a diffuse humeral spot. It differs from H. tortuguerae in the number of teeth on the maxilla (1-2), by the number of predorsal scales and the high number of scales between the lateral line and the anal fin (6-7). Hyphessobrycon chocoensis can be distinguished from the other known species of Hyphessobrycon from the Pacific Coast of Colombia in having: a high number of pored lateral-line scales, by the snout to dorsal-fin length, by caudal-peduncle depth and by eye diameter. In addition, it differs from H. columbianus by the distance from the dorsal fin to the anal fin, by the length of the upper jaw, and by snout length. It differs from H. condotensis in having a high number of scales between the lateral line and the dorsal fin, and by the number of simple rays in the anal fin. H. chocoensis is distinguished from H. sebastiani by the number of transverse scales and the number of scales between the lateral line and the dorsal fin. A taxonomic key is provided to aid with the identification of the species of Hyphessobrycon from the Pacific Coast of Colombia.